Calibration of input parameters in volcanic areas and an enlarged dataset by stochastic finite-fault simulations - Galluzzo, D. (2012)
The calibration of the input parameters is the important task for stochastic finite-fault simulation in volcanic areas that we manage in the framework of the european project UPStrat-MaFa. The stochastic simulation method requires to know fault geometry, source, crust properties of the region and local site effect. We focused on the following pilot test areas: Mt Vesuvius, Campi Flegrei and Mt Etna , performing also two application for large magnitude event for Azores Islands and South Iceland. A general preliminary database of ground motion records has been collected in all test areas in order to set up the empirical laws of ground motion parameters. The results of the simulations are compared with observed waveforms and response spectra, to evaluate the suitability of the used parameters. The results show a good agreement between observed and simulated time histories and response spectra, encouraging further effort towards quantitative high resolution studies on input parameters.